Penatalaksanaan Nyeri Reumatoid Athritis Di Balai Pelayanan Sosial Dewanata Cilacap 2022 - Fauziyah, Anisa Maharotun; Maryoto, Madyo (Universitas Pekalongan, 2022)
Rheumatoid arthritis is a disease that attacks the limbs namely joints, muscles, bones and tissues around the joints causing pain, swelling in the joints. This pain management is done by using red ginger compress therapy which aims to reduce pain in the joints. The aim is to analyze the results of the implementation of nursing care with the intervention of giving ginger compresses to the elderly to meet pain needs. The method in writing the Final Scientific Work is in the form of a case study taken while practicing at the Wisma 2 Social home Tresna Werdha Dewanata by doing nursing nurture for 3 times a week. The results obtained after the intervention showed that there was a reduction in pain during the giving of ginger compresses in the elderly with rheumatoid arthritis. There is a decrease in the scale of pain after red ginger compressing from before compressing ginger on the four pain scale, after compressing the red ginger on the pain scale for once. It is concluded that there is a significant effect on the giving of ginger compresses in the elderly who had rheumatoid arthritis. It is recommended for the institution to be able to apply the ginger compress intervention in addition to the pharmacological drugs that have been carried out by the orphanage.